Stench and sensibilities: On living with waste, animals and microbes in India. (2nd December 2020) - Doron, Assa
Abstract: Stench is often the most immediate mark of something dirty, decaying and diseased. In India, stench and the smell of acrid smoke commonly indicate the proximity of an open dump or landfill. Frequently a slum is located in the vicinity too, housing waste‐pickers who forage in these sprawling dumps for salvageable waste. These spaces are also host to vermin, birds, stray dogs, pigs, cows and, more recently, dangerous bacteria resistant to even top‐end antibiotics, popularly known as 'superbugs'. In this paper I examine the socio‐ecological context of neighbourhood, community open garbage dumps and larger landfills in an effort to understand these as part of a dynamic ecosystem of 'more‐than‐human' relations. Perceptual variations of smell as experienced in and around waste (in its solid, liquid and gas states) are intrinsically linked to symbolic and material practices across species. Additionally, I suggest that one productive way to think about the emergence of disease and pathogenicity is by considering the information stimulated by smell, which is mediated by cultural interpretations, biological capacities and wider political economies.